Relationships between lower body strength characteristics and initial acceleration coordination in highly trained to world class sprinters - Donaldson, B.; Bezodis, N. E.; Bayne, H. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Inter- and intra-limb coordination has recently been described in initial sprint acceleration [1]. From a dynamical systems perspective, coordination patterns emerge from interacting individual, task and environmental constraints [2]. Lower body strength is a key individual constraint in sprinting and influences sprint performance, but the interactions between strength characteristics and movement patterns are not yet known. This study aimed to assess the relationship between lower body strength and initial acceleration coordination in sprinters.